Beer culture in theory and practice : understanding craft beer culture in the United States - Tyma, Adam W., 1973- (Communication perspectives in popular culture., 2017)
The contributors of this collection explore various aspects and questions surrounding craft beer culture from perspectives of business, gender, community-building, branding, and culture.